MYC-PDL1 axis reduces sensitivity to nivolumab in recurrent head and neck squamous cell carcinoma. (January 2022) - Noji, Rika; Kano, Yoshihito; Hirai, Hideaki; Onishi, Iichiroh; Nishii, Naoto; Yoshimura, Ryoichi; Miyake, Satoshi; Ikeda, Sadakatsu; Harada, Hiroyuki
Abstract: Patients with recurrent or metastatic squamous cell carcinoma of the head and neck (R/M HNSCC) have a poor prognosis. Recently, the use of immune checkpoint inhibitors (ICIs) for drug treatment has been expanding . However, the response rate to immunotherapy is low. Therefore, the identification of predictive biomarkers of response and resistance to ICIs is required for various types of malignant tumors. We report the case of a patient with recurrent and metastatic HNSCC who simultaneously showed different responses to nivolumab in metastatic lesions. After administering nivolumab, metastasis to the multiple cervical lymph node metastases showed a significant reduction, whereas a new metastasis to the right axillary lymph node occurred . Each surgical specimen was analyzed using the cancer gene panel test (FoundationOne CDx) to elucidate why treatment response is distinct among the same patient. Next-generation sequencing revealed MYC amplification and programmed cell death-1 loss in the right axillary lymph nodes but not cervical lymph nodes. Furthermore, t he histopathological findings suggested that MYC amplification regulated programmed death-ligand 1 expression and was involved in a decreased response to ICIs. This result is expected to help predict the efficacy of ICI treatment and select therapeutic agents.